PENGEMBANGAN KAWASAN WISATA DANAU KELIMUTU Studi Efektivitas Pada Balai Taman Nasional Kelimutu Kabupaten Ende - Andrianto Umbu Ndjandji (Mimbar Administrasi Mandiri, 2024)
The achievement of the set goals or objectives in any organization, activity or program, if achieved by a particular method, depends largely on the approach by which those goals or objectives are achieved. Starawaj's theory with Martin and Lubis, whose size includes six indicators, including program success, objective success, program satisfaction, baseline approach, process approach, and goal approach, is the basis for measuring development effectiveness. This study used qualitative methodologies and descriptive narrative to describe the study findings. Efficiency theory can be used as a reference point for the successful development of Kelimutujärvi to achieve the goals based on the results of the study, although according to it the development is at the level of sustainable development. Proper development requires effective procedures, such as development through well-targeted programs.